Breast MRI in DCIS size estimation, breast-conserving surgery and oncoplastic breast surgery. (March 2021) - Bartram, Alexander; Gilbert, Fiona; Thompson, Alastair; Mann, G Bruce; Agrawal, Amit
Highlights: The utility of MRI in the detection and management of pure DCIS remains inconclusive. The impact of pre operative MRI on mastectomy rates is debated and the utility in oncoplastic breast surgery remains unexplored. MRI is likely to provide a more accurate estimate of tumour size, but does not improve outcomes in conventional breast conserving surgery. There is a paucity of data on the impact of pre-operative MRI in oncoplastic breast surgery. Abstract: The impact of MRI on improving surgical outcomes in DCIS is debated. Here, we explore the utility of MRI in the investigation and management of DCIS in three key areas. Firstly, we highlight that MRI is likely to be a more accurate predictor of actual tumour size than conventional imaging. Secondly, we examine mastectomy rates and reoperation rates across the literature and suggest that surgical outcomes do not differ between pre-operative MRI and conventional imaging groups, despite improved size estimation on MRI. Finally, we examine the rapidly developing field of oncoplastic breast surgery and highlight a paucity of data in determining the usefulness of pre-operative MRI in this field, despite this being an oncologically safe alternative with improved patient outcomes and satisfaction.